Migration Policy in the Era of Trumpism and Media Spectacle: What a 2024 Trump [or other] Presidency Could Mean for Mexico-U.S. Relations - Terence Garrett (Norteamérica)
Donald Trump may be the Republican presidential nominee for the 2024 election and is facing multiple indictments for alleged crimes committed during his presidency. If convicted, this would make a Trump election victory unlikely, although he is the master of the media spectacle and populist authoritarianism – essential components of Trumpism. I focus on U.S. migration policy consequences affecting Mexico and other states in the Americas if Trump wins in 2024. With a Republican win, the migration policy could revert back to a Title 42 migrant expulsion scenario, with attempts to harden the border using more personnel, infrastructure, and surveillance technology. President Biden, if reelected, is on a course towards increased militarization of the southwest border that is a long-term bipartisan trend with globalization – accelerated by Trumpism down to the U.S. state level. Analyzing these scenarios, the border securocracy theoretical concept is employed in keeping with Trumpism migration policies.